Interaccion de Rhizobium phaseoli y Azospirillum spp. en el cultivo del frijol (Phaseolus vulgaris L.) - Abreu Galan, J.I.=700 1 Liriano Gonzalez, R.; Sanchez Llanes, P.; Lima Diaz, S.
(Es, En)
Ilus., 5 ref.
Keywords: PHASEOLUS VULGARIS; AZOSPIRILLUM; RHIZOBIUM; SIMBIOSIS; DOSIS DE APLICACION; CUBA